Weevils, weevils, weevils everywhere* - Oberprieler, Rolf (2007)
An overview is presented of the progress made on the taxonomy, classification and phylogeny of weevils in the 250 years since the first taxonomic descriptions of weevils by Carolus Linnaeus. The number of described weevils species is calculated to be about 62 000 and the likely total number of existing species 220 000, indicating that we have described just over a quarter of the diversity of this important group of beetles and that, at current rates of discovery and description, it will take another 650 years or so to describe the rest. Within the framework of the current concept of weevil phylogeny, a brief account is given of the seven main weevil lineages (families), and of the subfamilies of the largest of them, the Curculionidae, summarising their diversity, distribution and biology and identifying the major classificatory problems remaining in each. In conjunction with the phylogenetic hypothesis of weevil relationships and their fossil record, which is briefly summarised, the evolutionary history of weevils is mapped as a sequence of key evolutionary innovations that together have led to the phenomenal diversification and success of weevils. Key words: Curculionoidea, diversity, classification, phylogeny, evolutionary history.